2017
DOI: 10.1183/13993003.02322-2016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis identifies sex-associated metabotypes of oxidative stress and the autotaxin–lysoPA axis in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease and a leading cause of mortality and morbidity worldwide. The aim of this study was to investigate the sex dependency of circulating metabolic profiles in COPD.Serum from healthy never-smokers (healthy), smokers with normal lung function (smokers), and smokers with COPD (COPD; Global Initiative for Chronic Obstructive Lung Disease stages I–II/A–B) from the Karolinska COSMIC cohort (n=116) was analysed using our nontargeted liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 52 publications
2
86
0
1
Order By: Relevance
“…Nine omics data blocks (figure 1) from 52 female subjects (20 Healthy,20 Smokers, 12 COPD) were used: mRNA from BAL cells collected by microarray [22]; miRNA from BAL cells and from exosomes from BAL fluid (BALF) collected by microarray [22,27]; difference gel electrophoresis (DIGE) proteomics from BAL cells [17]; shotgun proteomics data from BAL cells collected by isobaric tags for relative and absolute quantitation (iTRAQ) mass spectrometry (MS) [25,28]; shotgun proteomics data from BEC collected by means of tandem mass tag (TMT)-MS [29]; eicosanoid profiling data from serum and BALF [21]; and metabolomics data from serum [30]. For details regarding data collection platforms and data preprocessing, see previous publications and supplementary material.…”
Section: Omics Data Blocksmentioning
confidence: 99%
“…Nine omics data blocks (figure 1) from 52 female subjects (20 Healthy,20 Smokers, 12 COPD) were used: mRNA from BAL cells collected by microarray [22]; miRNA from BAL cells and from exosomes from BAL fluid (BALF) collected by microarray [22,27]; difference gel electrophoresis (DIGE) proteomics from BAL cells [17]; shotgun proteomics data from BAL cells collected by isobaric tags for relative and absolute quantitation (iTRAQ) mass spectrometry (MS) [25,28]; shotgun proteomics data from BEC collected by means of tandem mass tag (TMT)-MS [29]; eicosanoid profiling data from serum and BALF [21]; and metabolomics data from serum [30]. For details regarding data collection platforms and data preprocessing, see previous publications and supplementary material.…”
Section: Omics Data Blocksmentioning
confidence: 99%
“…These studies also support a hypothesis of FA oxidation and tryptophan metabolism dysregulation leading to a state of high oxidative stress. An effect on FA oxidation was also demonstrated in COPD participants by Naz et al who measured the ratio of carnitine and acylcarnitine using tandem LC–MS. The study found that the ratios between the medium‐ and long‐chain carnitines were significantly lower in the COPD samples compared to the healthy controls.…”
Section: Metabolomic‐driven Discovery Of Biomarkersmentioning
confidence: 64%
“…A number of recent studies have revealed metabolic dysregulation in COPD patients . For example, alterations in the sphingolipid metabolism was identified in COPD patients and patients in the Karolinska smoking‐related disease cohort, suggesting a dysregulation of lipid metabolism during the onset of COPD. This was further supported by the findings of Adamko et al who identified an increase in betaine and choline levels in COPD patients.…”
Section: Metabolomic‐driven Discovery Of Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…(COSMIC) cohort: The Karolinska COSMIC cohort (Clinical Trials ID: NCT02627872) is a cross-sectional study designed for investigating the molecular pathogenesis of COPD. Methods of tissue procurement, cohort characteristics, and gene expression profiling have been previously described and further details are provided in Supplementary Methods (18,44). MicroRNA profiling was performed on airway epithelial brushings collected by fiberoptic bronchoscopy in a subset of the Karolinska COSMIC cohort.…”
Section: Clinical and Systems Medicine Investigations Of Smoking-relatementioning
confidence: 99%